Overcoming barriers to technology transfer and business commercialisation in Central and Eastern Europe : solutions and opportunities - Bendis, Richard A.; Craciunoiu, Stefan T. (NATO science series. Science and technology policy, 2002)
In the 21st century, Central and Eastern Europe face challenges in respect to innovation and business development. The NATO - Advanced Research Workshop ""Overcoming Barriers to Technology Transfer and Business Commercialisation in Central & Eastern Europe"" was designed to allow pertinent organisations from different nations to share ideas and strategies to address these challenges. The thrust of the workshop was to improve the transformation process of R & D to home-grown technologies and ultimately, innovative and successful businesses. It is important to recognise that most Central and Easte